Flow Cytometric Clinical Immunomonitoring Using Peptide–MHC Class II Tetramers: Optimization of Methods and Protocol Development - Jansen, Diahann T. S. L.; Ramnoruth, Nishta; Loh, Khai L.; Rossjohn, Jamie; Reid, Hugh H.; Nel, Hendrik J.; Thomas, Ranjeny (Frontiers in Immunology, 2018)
With the advent of novel strategies to induce tolerance in autoimmune and autoimmune-like conditions, clinical trials of antigen-specific tolerising immunotherapy have become a reality. Besides safety, it will be essential to gather mechanistic data on responding CD4+ T cells in order to assess the effects of various immunomodulatory approaches in early-phase trials. Peptide-MHCII multimers are an ideal tool for monitoring antigen-specific CD4+ T cell responses in unmanipulated cells directly ex vivo. Various protocols have been published but there are reagent and assay limitations across laboratories that could hinder their global application to immune-monitoring. In this methodological analysis, we compare protocols and test available reagents to identify sources of variability and to determine the limitations of the tetramer binding assay. We describe a robust pMHCII flow cytometry-based assay to quantify and phenotype antigen-specific CD4+ T cells directly ex vivo from frozen PBMC samples, which we suggest should be tested across various laboratories to standardise immune-monitoring results.